Major Ion and Rare Earth Element Concentrations in Rainwaters from Ajdabiya, Benghazi and Al Marj, NE Libya: Natural and Anthropogenic Sources - O.R. Shaltami (Scientific Journal of University of Benghazi, 2026)
Rainwater samples collected from Ajdabiya, Benghazi and Al Marj, NE Libya have been analyzed for their rare earth elements (REE) and major ions. The major ion compositions of these samples show the contributions of oceanic, crustal, and anthropogenic sources, and suggest the relative importance of these sources. The studied samples have distinctly high SO4 and NO3 contents. The rainwater samples also have variable REE compositions with various enrichment of light REE over heavy REE. Rainwater samples from Ajdabiya and Benghazi are significantly enriched in light REE, whereas those collected in Al Marj have loess or shale-like REE composition. The enrichment of light REE in the Ajdabiya and Benghazi rainwater samples corresponds to the typical signature of an anthropogenic source. The Y/Ho ratios in the studied samples are all higher than average crustal values, and in general, increase with increasing enrichment of light REE. This indicates that physical mixing of crustal and oceanic sources of the REE cannot account for the variations of the Y/Ho ratios. Furthermore, although the anthropogenic source of the REE is generally characterized by a high Y/Ho ratio, factors such as particle/rainwater interactions, pH, and speciation of REE may also be responsible for the variable abundance and fractionation of REE and Y/Ho in the studied rainwaters.